2020
DOI: 10.20473/j.djmkg.v53.i1.p6-9
|View full text |Cite
|
Sign up to set email alerts
|

The different effects of preheating and heat treatment on the surface microhardness of nanohybrid resin composite

Abstract: Background: A composite resin is used as restorative material in dentistry because it has the same colour as dental enamel, is easy to use in an oral cavity and offers good biocompatibility. Based on the size of filler, composite resin is divided into types, one of which is a composite resin nanohybrid. An important mechanical property of restorative material is microhardness. The mechanical properties of restorative material is highly affected by both polymerisation and heating process. There are many methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…The provided table (Tables 3, 4) summarizes various studies on microhardness and fracture toughness. Out of the total 29 studies included, 16 demonstrate an increase in microhardness alone [3,8,9,12,13,15,16,17,18,19,21,22,23,25,27,28], while one shows an increase in fracture toughness alone [20]. Additionally, three studies reveal no statistically significant difference in microhardness values [5,10,30].…”
Section: Resultsmentioning
confidence: 97%
“…The provided table (Tables 3, 4) summarizes various studies on microhardness and fracture toughness. Out of the total 29 studies included, 16 demonstrate an increase in microhardness alone [3,8,9,12,13,15,16,17,18,19,21,22,23,25,27,28], while one shows an increase in fracture toughness alone [20]. Additionally, three studies reveal no statistically significant difference in microhardness values [5,10,30].…”
Section: Resultsmentioning
confidence: 97%
“…In aesthetic dental treatment, this restoration has many advantages over other treatments such as ceramic veneers and orthodontic treatments: they are more compatible with antagonistic teeth than ceramic materials, and if there is a fracture, it will be easier to repair because it does not require additional time and cost. [15][16][17] However, composite resins also have several disadvantages, including shrinkage during polymerisation, a low wear resistance, poor long-term durability, postoperative sensitivity and (in clinical use) direct composite resins have the potential to become secondary caries and fracture. 18,19 Digital smile design is a digital aesthetic planning tool in dentistry that is used to evaluate the aesthetic relationship between the teeth, gingiva, smile and face.…”
Section: Discussionmentioning
confidence: 99%
“…8 Preheating is a preparation method of composite resin which can improve composite physical and mechanical properties, with the increase in temperature, the polymers in composite turns more fluid making material more flowable, 9 thus reducing stress in the extrusion from syringe giving a better reaction resulting better cross link and polymerization that will lead to increase in mechanical strength and wear resistance. 10 The heating of composite resin is recommended by using Composite Heating Conditioner Micerium S.p.A Heater (Ena Heat, Micerium S.p.A., Avegno GE, Italy) which is designed with two temperature options 39°C and 55°C, with 39°C usually used to heat composite for restoration and 55°C for cementation. 11 Previous research by Valinoti, showed that immersion of nano filed composite resin in Claritin medicine with acidic pH 2.57 with pH-cycling method 4 times a day for 12 days show significant increase in nano filled composite resin surface roughness.…”
Section: Introductionmentioning
confidence: 99%